The Impact of PSA Screening on Pharmacological Management in Asymptomatic Men and Those with Lower Urinary Tract Symptoms - Nadeem Akhtar Korai, Abdul Basit Niazi, Syed Raza Abbas, Anum Ashraf, Usman Saeed, Muhammad Shakeel Anjum, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: To evaluate the impact of Prostate-Specific Antigen (PSA) screening on the initiation and type of pharmacological management in two distinct cohorts: asymptomatic men undergoing routine health check-ups and symptomatic men presenting with Lower Urinary Tract Symptoms (LUTS). Study Duration: November 2022 to June 2023. Study Place: Rai Foundation Medical College, Sargodha. Methodology: A prospective cohort study included 450 men aged 50–75. Group A had 225 symptom-free people, while Group B had 225 LUTS patients. All participants took the PSA test. PSA and clinical observations guided pharmaceutical therapy documentation and classification. Results: PSA screening significantly improved pharmacological therapy in both groups. Due to increased PSA results, 18.2% of asymptomatic Group A patients needed medication following screening, mostly 5-alpha reductase inhibitors (5-ARIs). In symptomatic Group B, 76.4% of individuals took phosphodiesterase-5 inhibitors, alpha-blockers, and 5-ARIs. PSA levels directly affected treatment aggressiveness, especially with the exclusion of prostate cancer as a cause of LUTS. Conclusion: PSA screening alters pharmaceutical management. It identifies asymptomatic males who need early BPH treatment or cancer screening. Diagnostics and treatment are more accurate and effective when administered to symptomatic guys. PSA improves urological therapy, even though it's not ideal. Keywords: Prostate-Specific Antigen, PSA Screening, Pharmacological Management, Lower Urinary Tract Symptoms, Asymptomatic Men, Benign Prostatic Hyperplasia.